Studi Kasus Mariani Songket: Pemanfaatan Media Sosial Untuk Membentuk Personal Branding Sebagai Bentuk Komunikasi Bisnis - Martha Cristina Br Panjaitan; Lampola Sitorus P; Enjel Carlina Sihombing; Monica Lance Sinaga; Tahan Maruli Jaya Gultom; Andreas Mian Asiniroha Pasaribu; Fernando Pasaribu (LPPM Universitas HKBP Nommensen, 2025)
This research focuses on the use of social media in shaping personal branding as a business communication tool at Mariani Songket, a traditional songket craft business. The research used a qualitative case study approach, with analysis including observation of digital content on social media platforms and a literature review. The results show that Mariani Songket's authentic personal branding, which tells the story of the production process and cultural stories, increases audience loyalty and product appeal. Social media is not just a promotional tool, but also a space for education and cultural preservation. These findings confirm that the integration of digital communication with personal branding contributes significantly to the growth of traditional creative businesses and offers a strategic model for other MSMEs.